Highly Sensitive Triple-Band THz Metamaterial Biosensor for Cancer Cell Detection - Ahmed Refaat Elhelw; Mahmoud Salman S. Ibrahim; Ahmed Nabih Zaki Rashed; Abd El-Naser A. Mohamed; Mohamed Farhat O. Hameed; Salah Sabry Ahmed Obayya (IEEE Photonics Journal)
Highly sensitive triple-band metamaterial-based biosensor for different cancer cells detection is suggested and numerically analyzed. The reported sensor has a polyimide dielectric layer which is sandwiched between gold bottom plane and top metallic patches. The analyte sample covers the metallic patch where multiple resonances occur with high absorption. The resonance frequencies depend on the optical properties of the analyte sample. Therefore, the proposed sensor can distinguish between different cancer cell types such as skin cancer, blood cancer, and Breast cancer. Full vectorial finite element method is used to study the effects of the geometrical parameters with the aim to maximize the sensor sensitivity. The suggested sensor has high sensitivity of 2050 GHz/RIU (which is much higher than those suggested in the literature) with high quality factor of 55.34 in the frequency range from 4.25 THz to 4.75 THz. Further, the proposed biosensor is a label-free, and easy for fabrication using the state-of-the-art fabrication technologies.